Millennial cinema: memory in global film - Sinha, Amresh, and McSweeney, Terence, (A Wallflower book, 2011)
In spite of the overwhelming interest in the study of memory and trauma, no single volume has yet explored the centrality of memory to films of this era in a global context; this volume is the first anthology devoted exclusively to the study of memory in twenty-first-century cinema. Combining individual readings and interdisciplinary methodologies, this book offers new analyses of memory and trauma in some of the most discussed and debated films of the new millennium: 'Pan's Labyrinth' (2006), 'The Namesake' (2006), 'Hidden' (2005), 'Eternal Sunshine of the Spotless Mind' (2004), 'Oldboy' (2003), 'City of God' (2002), 'Irreversible' (2002), 'Mulholland Drive' (2001), 'Memento' (2000), and 'In the Mood for Love' (2000)
https://katalog.adlr.link/Record/155-1601168527